Unlocking the jar: revealing gastric content in Ceriantharia (Cnidaria, Anthozoa) through whole-genome shotgun sequencing - Santos, Thaís Barbosa [UNESP]; Poliseno, Angelo; Bendia, Amanda G.; Pellizari, Vivian H.; Reimer, James D.; Stampar, Sérgio N. [UNESP] (Springer Nature, 2024)
This study focuses on the analyses of the gastral cavity contents of two species of Ceriantharia, namely Isarachnanthus nocturnus Hartog, 1977, collected in São Sebastião, Brazil, and Pachycerianthus magnus Nakamoto, 1919, collected from two points along the coast of Okinawa Island, Japan. Both morphological (light microscopy) and metagenomic (whole-genome shotgun sequencing) analyses were conducted with the aim of identifying the main classes of organisms that make up the diet of these species. The results revealed that morphological analyses were not sufficient for identifying prey organisms, but metagenomic analyses showed a diverse range of animal classes, indicating the varied diet of these ceriantharians. The most abundant classes observed in the contents of both species were Anthozoa, Aconoidasida, Kinetoplastea, Actinopterygii, Insecta, and Leptocardii. This finding suggests a cohesive feeding pattern among these two species from distant areas, providing a more comprehensive understanding of their feeding performance and contributing to studies on the subclass Ceriantharia.
Keywords: Diet; Food web; Gastral cavity contents; Metagenomics; Tube-dwelling anemones